1998
DOI: 10.1007/s005350050112
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholangiocarcinoma with increased serum CYFRA 21-1 level

Abstract: CYFRA 21-1 is a fragment of cytokeratin 19 (CK 19). Four patients with large intrahepatic (or peripheral) cholangiocarcinoma (CC) and high serum levels of CYFRA 21-1 (normal, < or = 2 ng/ml) are reported. CYFRA 21-1 levels exceeded 9 ng/ml in all 4 patients. Carcinoembryonic antigen (CEA), was high in 1 (CEA; normal range, < or = 5.0 ng/ml) and carbohydrate antigen 19-9 (CA 19-9) was high in 3 (CA19-9; normal range, < or = 36 U/ml). We also measured serum levels of CYFRA 21-1 in 13 patients with hepatocellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…Kubo et al (1995) reported that a high-serum CEA concentration strongly suggests ICC in patients with hepatolithiasis, even when no hepatic tumour is detected. Generally, however, serum CEA concentrations are elevated in only 20 -45% of patients with ICC (Yamanaka et al, 1995;Chu et al, 1997;Harrison et al, 1998;Kashihara et al, 1998;Kim et al, 1999;Uenishi et al, 2001). In the present study, serum CEA also showed a low sensitivity for ICC (34.8%).…”
Section: Cyfra 21-1 and Pathologic Variables In Patients With Icccontrasting
confidence: 68%
See 2 more Smart Citations
“…Kubo et al (1995) reported that a high-serum CEA concentration strongly suggests ICC in patients with hepatolithiasis, even when no hepatic tumour is detected. Generally, however, serum CEA concentrations are elevated in only 20 -45% of patients with ICC (Yamanaka et al, 1995;Chu et al, 1997;Harrison et al, 1998;Kashihara et al, 1998;Kim et al, 1999;Uenishi et al, 2001). In the present study, serum CEA also showed a low sensitivity for ICC (34.8%).…”
Section: Cyfra 21-1 and Pathologic Variables In Patients With Icccontrasting
confidence: 68%
“…Therefore, a soluble fragment of cytokeratin 19, CYFRA 21-1, may be a useful marker for ICC. Kashihara et al (1998) have reported that high serum concentrations of CYFRA 21-1 in patients with large liver cancer would suggest the existence of ICC rather than HCC, since serum concentration of CYFRA 21-1 markedly elevated in four patients with ICC, compared with that in 13 patients with HCC. However, all the four patients had severe advanced and unresectable tumours.…”
Section: Cyfra 21-1 and Pathologic Variables In Patients With Iccmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Circulating fragment, the cytokeratin 19, using the CYFRA 21-1 assay has been shown to be elevated in CC, with a sensitivity of 74.7% and specificity of 92.2%. 21,22 It has been suggested that the increased concentration of CYFRA 21-1 might represent circulating tumor cells and that surgery alone may not be able to control CC in patients with a high CYFRA 21-1 concentration. 22 In a study published in this journal by Chapman et al, CYFRA 21-1 and CA 19-9 levels have been evaluated in 66 patients with BTC (PSC related, 6; sporadic, 60), 39 patients with benign biliary disease, and 19 patients with PSC.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial report of CYFRA 21-1 by Kashihara et al in 4 cases of biliary cancer, there are scant data of this biomarker. 21 The sensitivity of CYFRA 21-1 in BTC is poor. As an isolated test result, this will make a poor biomarker for diagnosis, though it is possible that it may have a role as a part of a biomarker panel, including CA 19-9.…”
Section: Introductionmentioning
confidence: 99%